2015
DOI: 10.1242/jcs.169961
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone-induced cellular tension requires SGK1-stimulated Sec5/GEF-H1 interaction

Abstract: Dexamethasone, a synthetic glucocorticoid, is often used to induce osteoblast commitment of mesenchymal stem cells (MSCs), and this process requires RhoA-dependent cellular tension. The underlying mechanism is unclear. In this study, we show that dexamethasone stimulates expression of fibronectin and integrin α5 (ITGA5), accompanied by an increase in the interaction of GEF-H1 (also known as ARHGEF2) with Sec5 (also known as EXOC2), a microtubule (MT)-regulated RhoA activator and a component of the exocyst, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…We also observed that cells in the HA‐Pam‐Mg·Dex group mainly maintained a spherical morphology, whereas cells in the former two groups exhibited more isotropic spreading, as evidenced by the larger cell area and smaller sphericity (Figure c,d). It has been reported that Dex can stimulate expression of fibronectin and integrin at cell adhesion sites, which are essential to cell spreading and generation of cellular tension . Thus, sustained supply of Dex in the HA‐Pam‐Mg&Dex and HA‐Pam‐Mg‐DexP group may promote the cellular adhesion and interaction with the hydrogel network, thereby facilitating the spreading of encapsulated cells.…”
Section: Resultsmentioning
confidence: 99%
“…We also observed that cells in the HA‐Pam‐Mg·Dex group mainly maintained a spherical morphology, whereas cells in the former two groups exhibited more isotropic spreading, as evidenced by the larger cell area and smaller sphericity (Figure c,d). It has been reported that Dex can stimulate expression of fibronectin and integrin at cell adhesion sites, which are essential to cell spreading and generation of cellular tension . Thus, sustained supply of Dex in the HA‐Pam‐Mg&Dex and HA‐Pam‐Mg‐DexP group may promote the cellular adhesion and interaction with the hydrogel network, thereby facilitating the spreading of encapsulated cells.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the junctional adaptor cingulin recruits GEF-H1 to tight junctions thereby inactivating its GEF activity and inhibiting Rho signaling ( Aijaz et al, 2005 ). By contrast, the interaction of GEF-H1 with Sec5 promotes RhoA activation at the exocyst complex ( Pathak et al, 2012 ) and is important for GEF-H1 localization to FAs ( Wang et al, 2015 ). Recently, plasma membrane associated active RhoA was demonstrated to recruit GEF-H1 thereby promoting a self-amplification loop.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that SGK1, the mammalian homologue of Ypk1 (Casamayor et al, 1999), facilitates PM recycling of KCNQ1 channels in a Rab5-dependent manner, but whether that behavior was dependent on SGK1-mediated phosphorylation of any Rab5 GEF was not explored (Seebohm et al, 2008). Likewise, it has been reported that SGK1 function promotes association of a Rho- and Rac-specific GEF (ARHGEF2/GEF-H1) with a component (Sec5/EXOC2) of the mammalian exocyst complex, but again whether that behavior was dependent on SGK1-mediated phosphorylation of the GEF was not determined (Wang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%